Game Theoretic Analysis of the Feedback Loop Caused by Widely Available Computer Estimation on Market Values - Viorel Silaghi; Zobaida Alssadi; Ben Mathew; Majed Alotaibi; Ali Alqarni; Marius Silaghi (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Public availability of computer generated predictions can change the markets and its impact is here investigated with a game theoretic approach. Real estate inflation is not a new phenomenon but its consistent and almost monotonous persistence over unusually many years, coinciding with new prominence of public estimation information from successful Mass Real Estate Estimators (\MREE{}) already caused various independent research organizations to investigate potential links. What we model is a repetitive theoretical game between the MREEs and the home owners, where each player has secret information and expertise. In contrast to competing results, for our model and simulations a restriction of MREE-style price estimation availability to opt-in properties may help partially reduce an inflationary pressure.